A Note on Comparison Between the Wiener Index and the Zagreb Indices (Communications in Mathematical Research, 2019)
In this note, we correct a wrong result in a paper of Das et al. withregard to the comparison between the Wiener index and the Zagreb indices for trees(Das K C, Jeon H, Trinajstić N. The comparison between the Wiener index and theZagreb indices and the eccentric connectivity index for trees. Discrete Appl. Math.,2014, 171: 35–41), and give a simple way to compare the Wiener index and the Zagrebindices for trees. Moreover, the comparison between the Wiener index and the Zagrebindices for unicyclic graphs is carried out.
Keywords: Wiener index; Zagreb indice; tree; unicyclic graph